Assessment of Information Literacy Skills of Postgraduate Students: Case of Rawalpindi Medical University, Rawalpindi - Shahzad, Amir; Sabzwari, Naushad; Farid, Ghulam; Afzal, Amir; Kamran, Muhammad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The study also highlights the major challenges to obtaining competences in IL in medical universities as well as hidden impediments. Aiming to raise medical postgraduate students’ self-awareness on their IL skills Administrators, librarians, academics, and policymakers will find the findings interesting. Aim: To advance understanding of how workplace-related aspects impact information literacy skills and to further develop a strategy for the emergence of IL mentality in the medical field workers and to more fully comprehend the benefits & drawbacks of present IL initiatives, an analysis with these factors would be beneficial. Methods: A study was conducted at Rawalpindi Medical University (RMU) among postgraduate students. Respondents working in public hospitals were given questionnaires for the survey and DAIs under consideration between February and May 2022. The study examined medical students’ attitudes, levels of awareness, and computer and internet usage skills. The research method was convenience sampling, as it was difficult to obtain a list of PGs from the university or hospitals due to privacy concerns and time and money constraints. A total sample of 577 doctors (88% response rate) filled out the entire form. The study aimed to assess the depth of postgraduate students’ abilities to deal with information literacy and their attitudes and current practices. Results: The research involved 323 postgraduate doctors who were undergoing four-year training at three public sector teaching hospitals in Pakistan. The majority of the participants were from the gynae, medicine, pediatrics, surgery, anesthesia, radiology, and ENT departments. The study also analyzed the average score of postgraduate trainees’ information literacy skills with the distribution of their gender. There were no statistically significant differences between male and female participants, as most responses indicated "upto my requirement" or "somewhat=3." An independent sample t-test was used to compare the average score of postgraduate trainees’ attitude towards their level of information literacy with the distribution of their gender. Practical Implication: The study indicates that there are no appreciable variations in the information literacy abilities and attitudes of male and female participants in medical education, indicating that both sexes have equal access to resources and opportunities. Additionally, it implies that knowing the average information literacy proficiency of postgraduate trainees can be useful in pinpointing areas where training curricula need to be improved. Conclusion: The study examined the information literacy attitudes and skills of 323 postgraduate doctors employed in Pakistan’s public hospitals. Gender disparities may not be a serious issue if there are no obvious differences between them in terms of attitudes or skills. However, regardless of gender, training and resources for all trainees can be enhanced